The Relationship between Emotional Intelligence and Aggressive Behavior in Early Adult Individuals Who Play Online Games - Fajar A Nawir; Widyastuti .; Ismalandari Ismail (Polteknik Ilmu Pemasyarakatan, 2023)
Aggressive behavior in early adult individuals who play online games can cause serious problems if they do not have emotional intelligence. This research is a study that aims to determine the relationship between emotional intelligence and aggressive behavior in early adulthood individuals who play online games. The sample in this study were early adults who played online games aged 18-25 years. The technique used in this research is incidental sampling, with several subjects as many as 599 respondents. The research data were analyzed using the Spearman Rho correlation. The results of the correlation test had a fairly strong and significant relationship, r = -0.483; p < 0.05. Implications of this research can be a reference for further researchers and for information that is important for online gaming users to implement or train emotional intelligence.